2006
DOI: 10.1073/pnas.0509144103
|View full text |Cite
|
Sign up to set email alerts
|

Indispensability of the glutamate transporters GLAST and GLT1 to brain development

Abstract: Previous in vitro studies have shown that the neurotransmitter glutamate is important in brain development. Paradoxically, lossof-function mouse models of glutamatergic signaling that are generated by genetic deletion of glutamate receptors or glutamate release show normal brain assembly. We examined the direct consequences on brain development of extracellular glutamate buildup due to the depletion of the glutamate transporters GLAST and GLT1. GLAST͞GLT1 double knockout mice show multiple brain defects, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 47 publications
2
92
2
Order By: Relevance
“…3D). It is reported that expressions of PECAM-1 and GLT1 start in cerebral microvessels prior to structural maturity of the BBB (Lossinsky and Wisniewski, 1998;Matsugami et al, 2006). This analysis showed that cerebrovascular angiogenesis is altered in the mutant mice.…”
Section: Glial Bmpria Signaling Is Essential For the Termination Of Amentioning
confidence: 70%
“…3D). It is reported that expressions of PECAM-1 and GLT1 start in cerebral microvessels prior to structural maturity of the BBB (Lossinsky and Wisniewski, 1998;Matsugami et al, 2006). This analysis showed that cerebrovascular angiogenesis is altered in the mutant mice.…”
Section: Glial Bmpria Signaling Is Essential For the Termination Of Amentioning
confidence: 70%
“…10 Moreover, the lack of EAAT1 and EAAT2 results in morbidity associated with developmental abnormalities such as impaired neuronal migration, indicating the essential role of EAATs in brain development. 12 Glutamate also has age-specific trophic effects in the developing cortex. 3 Although EAATs are not the only glutamate transporters expressed by CMECs, 6 the differential expression patterns of the EAATs in microvessels suggest that glutamate effects in the immature cortex are not subject to the same regulatory processes as in adulthood regarding brain-to-blood efflux.…”
Section: Discussionmentioning
confidence: 99%
“…Mice singly mutant for GLAST or GLT-1 are viable (Tanaka et al, 1997;Watase et al, 1998), but double-knock-out mice die in utero and exhibit multiple proliferation and migration defects of stem cells and/or neurons in cortex, hippocampus, and olfactory bulb (Matsugami et al, 2006). As in Drosophila, glutamate neurotoxicity was not readily apparent in double-mutant mice, but the neuroanatomical defects observed in mice may reflect added importance for glutamate-and activity-dependent processes in the development of mammalian nervous systems.…”
Section: Discussionmentioning
confidence: 99%